Pediatric lymphomas in Brazil - Gabriela Gualco; Claudete E. Klumb; Glen N. Barber; Lawrence M. Weiss; Carlos E. Bacchi (Clinics, 2010)
OBJECTIVE: This study provides the clinical pathological characteristics of 1301 cases of pediatric/adolescent lymphomas in patients from different geographic regions of Brazil. METHODS: A retrospective analyses of diagnosed pediatric lymphoma cases in a 10-year period was performed. We believe that it represents the largest series of pediatric lymphomas presented from Brazil. RESULTS: Non-Hodgkin lymphomas represented 68% of the cases, including those of precursor (36%) and mature (64%) cell origin. Mature cell lymphomas comprised 81% of the B-cell phenotype and 19% of the T-cell phenotype. Hodgkin lymphomas represented 32% of all cases, including 87% of the classical type and 13% of nodular lymphocyte predominant type. The geographic distribution showed 38.4% of the cases in the Southeast region, 28.7% in the Northeast, 16.1% in the South, 8.8% in the North, and 8% in the Central-west region. The distribution by age groups was 15-18 years old, 33%; 11-14 years old, 26%; 6-10 years old, 24%; and 6 years old or younger, 17%. Among mature B-cell lymphomas, most of the cases were Burkitt lymphomas (65%), followed by diffuse large B-cell lymphomas (24%). In the mature T-cell group, anaplastic large cell lymphoma, ALK-positive was the most prevalent (57%), followed by peripheral T-cell lymphoma, then not otherwise specified (25%). In the group of classic Hodgkin lymphomas, the main histological subtype was nodular sclerosis (76%). Nodular lymphocyte predominance occurred more frequently than in other series. CONCLUSION: Some of the results found in this study may reflect the heterogeneous socioeconomical status and environmental factors of the Brazilian population in different regions.